Phosphorylation and turnover of paxillin in focal contacts is controlled by force and defines the dynamic state of the adhesion site. Issue 2 (7th February 2015) - Qin, Ruifang; Schmid, Heidrun; Münzberg, Christin; Maass, Ulrike; Krndija, Denis; Adler, Guido; Seufferlein, Thomas; Liedert, Astrid; Ignatius, Anita; Oswald, Franz; Eiseler, Tim; von Wichert, Götz
<x xml:space="preserve">Abstract</x> Micro‐environmental clues are critical to cell behavior. One of the key elements of migration is the generation and response to forces. Up to now there is no definitive concept on how the generation and responses to cellular forces influence cell behavior. Here, we show that phosphorylation of paxillin is a crucial event in the response to exogenous forces. Application of force induced growth of adhesion sites and this phenomenon was accompanied by a downregulation of Src family kinase activity, which in turn led to a decrease in the phosphorylation of paxillin at the tyrosine residues Y31 and Y118. The force‐dependent growth of adhesion sites is mediated by a decrease in the turnover‐rate of paxillin in focal contacts. This turnover critically depended on the phosphorylation state of paxillin at Y31/118. Paxillin is an important regulator in the control of the aggregate state of the whole adhesion site since the turnover of other adhesion site proteins such as vinculin is influenced by the phosphorylation state of paxillin as well. Taken together these data suggest that SFK dependent phosphorylation of paxillin is a crucial event in the regulation of adhesion site function in response to force. © 2015 Wiley Periodicals, Inc.